Pengaruh Money Ethics dan Tax Morale terhadap Persepsi Mahasiswa Mengenai Tax Evasion dengan Hedonisme sebagai Variabel Moderasi: (Studi pada Organisasi Gerakan Mahasiswa Nasional Indonesia (GMNI) Mojokerto) - Putri Nurmala Aprilia; Hari Setiono; Muhammad Bahril Ilmiddaviq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research raises the issue of the phenomenon of tax evasion amidst the increase in tax revenue realization in the last three years. This study aims to determine the effect of money ethics and tax morale on student perceptions of tax evasion with hedonism as a moderating variable. The object of this research is the cadre of the Mojokerto National Student Movement (GMNI) organization. This study uses a quantitative approach with primary data sources and uses a survey method through google form with a Likert scale measuring instrument. The population in this study were 115 cadres of the Mojokerto GMNI organization. The sampling technique used purposive sampling to get 65 respondents. The data analysis technique uses descriptive statistical analysis with the Structural Equation Modeling- Partial Least Square (SEM-PLS) method. The test tool used is SmartPLS software version 4.1.0.2 with outer model and inner model. The results showed that money ethics has a positive and significant effect on student perceptions of tax evasion, tax morale has a negative and significant effect on student perceptions of tax evasion, and hedonism is able to moderate the influence of money ethics and tax morale on student perceptions of tax evasion.